A Mathematical Model for Describing the Rheological Behaviour of Skin Gelatine Extracted from the Caspian Sea Huso huso. Issue 1 (2nd January 2020) - Mahjoorian, Abbas; Jafarian, Sara; Fazeli, Fatemeh; Saeidi Asl, Mohammad Reza
ABSTRACT: The effects of different extraction methods (I, II, III, and IV), including two levels of acetic acid (0.2–2.0 N) and sodium hydroxide (0.2–2.0 N), on the skin gelatin extracted from Caspian Sea Huso huso skin was investigated. Furthermore, the gelatin extraction yield, melting point, viscosity, and sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) electrophoresis pattern of the solutions was studied. Based on preliminary experiments, thawed skins (weight, 50 g) were added to a flask containing four volumes of different sodium hydroxide solutions for 60 min at 7°C. Treated skins were washed thoroughly with excess cold water, rinsed with cold-distilled water, and then, treated with acetic acid. Skins were drained using cheesecloth. Afterward, the extraction of gelatin was performed in four volumes of distilled water in a water bath for 16–18 h. Results showed that the higher melting point belonged to method II, while the uppermost amount of yield and viscosity could be observed in method III. Method III had the highest level of acetic acid (2 N) and the lowest level of sodium hydroxide (0.2 N) among the other samples. High acetic acid concentration caused greater degradation of collagen cross-links, which resulted in the extraction of more protein compounds than sodium hydroxide; therefore, an increase in extraction yield and viscosity was observed. The gelatin viscosity decreased with increasing sodium hydroxide concentration (methods II and IV), while it increased with smaller amounts (methods I and III). Modelling results showed that the power-type model described the influence of soluble solids better than exponential-type model on the viscosity of the mentioned polymer.